Dinamika Pembelajaran Matematika dalam Konteks Pandemi COVID-19: Sebuah Analisis Bibliometrik: DYNAMICS OF MATHEMATICS LEARNING IN THE CONTEXT OF THE COVID-19 PANDEMIC: A BIBLIOMETRIC ANALYSIS - Fatmawati Payopo; Sitra Kalauw; Ria Kilala; Yenni Sauli; Hamila Hulihulis; Jackonias Sanadi; Muhammad Fathurrahman; Ismail Djakaria (KAMBIK: Journal of Mathematics Education, 2024)
This study presents a systematic literature review on the integration of mathematics and COVID-19, focusing on how the pandemic has transformed educational practices into online learning and emphasized the importance of mathematical modeling in understanding and managing virus spread. Utilizing qualitative methodology, this research processes data from articles sourced from the Dimensions database, analyzed using VOSviewer for bibliometric mapping. The findings indicate a significant shift in teaching practices, with the rapid adoption of digital technologies facilitating online mathematics education. This transition not only highlights the flexibility of digital platforms but also the challenges in engaging students and effectively conveying complex mathematical concepts remotely. Additionally, the review reaffirms the critical role of mathematical modeling in predicting the pandemic's trajectory and informing public health strategies. The study also explores the broader implications of these shifts, suggesting that the integration of technology in mathematics education, triggered by the pandemic, may have long-lasting effects on pedagogical approaches. Challenges such as technology access inequality and the need for pedagogical adjustments to optimize online learning environments are discussed. This research contributes to the academic discourse by mapping the evolution of mathematical applications during a global health crisis and suggests directions for future research to enhance the resilience of educational systems against similar disruptions.